The influence of peer’s social networks on adolescent’s cannabis use: a systematic review of longitudinal studies - Torrejón-Guirado, María-Carmen; Baena-Jiménez, Miguel Ángel; Lima-Serrano, Marta; de Vries, Hein; Mercken, Liesbeth (Frontiers in Psychiatry, 2023)
Aim: A systematic review was performed to summarize the key findings of the peer influence on cannabis use through Social Network Analysis (SNA) studies and identify limitations and gaps with the purpose of informing future research and practice. Longitudinal studies were included since they provide robust information about social relationships change over time.Background: Adolescents' cannabis use is a global problem, which has awakened an interest in its determinants such as social influences. Research has shown the importance of these influences on cannabis uptake and use. SNA is an useful relational approach to examine socialization mechanisms related to the onset of cannabis use in adolescents.A search was conducted in PyscINFO, PubMed, Scopus and Web of Science for longitudinal articles published until February 2023, to examine cannabis use and peer's social networks. We focus on peers' influence of peers on cannabis use. Additionally, information about effect of cannabis use for peer selection was collected. This is a provisional file, not the final typeset article Results: The results of the included studies (n=8) showed that friends' cannabis use was most often/strongly associated with cannabis use. There was also an increase of cannabis use when the adolescent did not feel close to the school's peers, had a higher proportion of friendships relative to the total number of ties in the neighbourhood, had a central position, did not belong to any group but had ties to members of two or more groups, had cannabis user friends (especially in early ages), and lived in a neighbourhood where cannabis was used.Conclusions: Cannabis use is mainly related to friends' use. Yet, future studies are warranted to control for relevant selection effects to further knowledge on network effects on cannabis use, improving the design, and improving the modelling of the network. This systematic review may inform about the critical aspects of preventing cannabis use among adolescents, taking into consideration their complex social environment.